Sosialisasi Strategi Bisnis Menggunakan Business Model Canvas (BMC) Pada Perusahaan Konstruksi - Sri Hartini; Tri Novita Sari; Masri Pradipto; Sri Nuryati (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
CV. Marga Jaya Properti started its business in marble, natural granite, granite tile, traso, wood interior and developed in the field of construction services such as construction and renovation services for residential houses, hospitals and places of worship. The high business competition makes it difficult for companies to market which results are decreased sales and decreased production. This activity aims to analyze the business in order to overcome these problems by socializing the business model design using the Business Model Canvas (BMC) method. The BMC method is carried out by observation, literature study and Focus Group Discussion (FGD) between the Team and the experts. Companies must increase marketing activities, increase product added value and increase partnerships. Marketing activities should be carried out both online and offline. Online marketing can be added through online buying and selling forums, google ads, tik tok shop, twitter, email or telegram, while offline marketing can be added by participating in property exhibitions, distributing brochures, holding property webinars, and inviting customer to become marketing. The increase in added value can be done by free consultations for construction service, free delivery product for Bekasi area. The increase partnerships is by adding developers such as developers for handling electricity, water and so on in working on large projects, for example the construction of hospitals. The results of this Activity that are felt by owners and employees are their increased knowledge of business models which can increase marketing, increase sales and increase production.